Tantangan Berat Bagi Lulusan Prodi Pendidikan Agama Islam - Rahimudin (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
The role of Islamic Religious Education teachers in schools is not just teaching or delivering material to students. But there is a big responsibility that is carried out, namely forming a noble person/character who has a moral character. Therefore, PAI Study Program graduates and PAI teachers in addition to being required to master the material must also have a noble character, love their profession, master various methods, models, and learning approaches. The purpose of this paper is the author wants to provide information to graduates of PAI study programs about the real conditions that exist in schools being faced by PAI teachers. Problems that exist in students are very complex starting from personal problems, family, and the environment in which students live. The conclusion of this study is that the various problems of students in the school are challenges that must be faced wisely so that the main objective of Islamic Religious Education in shaping humanity with moral values ​​can be realized properly. This paper is expected to provide motivation for PAI Study Program Graduates and PAI teachers to have mental readiness in dealing with various student problems at school. And no less important is PAI graduates and PAI teachers must be sincere in carrying out the mandate they carry and be able to establish communication and cooperation with all components in the school including parents of students.